Exploring AI adoption by Finnish Marketing Managers in Their International Marketing Actions - Tornberg, Renne (My University, 2024)
Artificial intelligence (AI) is attracting considerable interest worldwide due to its ability to produce favorable results across various fields and industries. The use of AI has grown ex-ponentially in recent years, and one area where it is predicted to bring even the most benefits out of all business areas is marketing. Systems utilizing AI have increasingly facili-tated manual and time-consuming tasks. Technological development seems to have pro-gressed to the point that it is predicted to be usable even in strategic thinking tasks. The possibilities of using AI in marketing are limitless, and some of the most potential areas are personalized advertising, recommendation systems, segmentation and targeting of customer groups, and market research. AI can bring significant benefits to a marketing manager doing international marketing, who must navigate different economic, political, legislative and cultural challenges posed by varying markets. Since the field of interna-tional marketing is more challenging than purely domestic marketing, it requires more extensive skills and competence from the manager. This is where AI can significantly ex-pand a person's abilities. The aim of this study is to explore the utilization of AI by Finnish marketing managers in their international marketing actions via the case study method. The research is qualitative in nature, and three marketing managers who work in Finnish international companies were interviewed. The sizes of the companies where the inter-viewees worked varied from a start-up to a multinational corporation, which affected their AI utilization strongly. Research data was collected using a semi-structured interview method, and thematic analysis was used to analyze it. The results of the study show that the interviewed marketing managers benefited from AI applications significantly despite the fact that these systems sometimes lack quality, and that they mostly used generative AI applications in their work. These were especially used for creating text content, lan-guage translations, ideation, but also for strategic planning. AI was felt to be most im-portant in the initial phase of tasks, where it accelerated getting started. However, the quality of the AI outputs has room for improvement, and they cannot be used until they have been first proofread and edited. Human control over AI was felt to be of primary importance. AI also included significant challenges, the biggest being information security threats and the quality of AI outputs. One interesting observation was the need for so-called “local AI” products, which would better understand market-specific differences in, for example, ways of communication. This is also an interesting topic for further research.
Keywords: markkinointi; tekoäly; liiketoiminta; markkinointiviestintä; kansainvälisyys; kansainvälinen markkinointi; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business